2010
DOI: 10.1111/j.1365-2621.2010.02469.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of porous starch preparation by ultrasonic pretreatment followed by enzymatic hydrolysis

Abstract: Porous starch granules were formed by the partial hydrolysis of starch using amylase. Fungal amylase and corn starch were chosen as the original amylase and substance from different sources, respectively. Ultrasonic technique as an assistant of enzymatic hydrolysis was used to pretreat raw starch. Scanning electron microscopy was used to examine the structure of native and treated starch, revealing the size of the pores in each occasion. The extent of enzymatic hydrolysis (y%) was markedly enhanced by statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 12 publications
0
15
0
3
Order By: Relevance
“…(However, SEM photomicrographs in their paper show that preparations made by ultrasonic treatment after digestion with the enzyme were the most porous and apparently had the largest surface area.) Qian et al (2010) pretreated starch with ultrasound before using an amylase to make porous starch. Z.…”
Section: Preparation Of Porous Starchmentioning
confidence: 99%
“…(However, SEM photomicrographs in their paper show that preparations made by ultrasonic treatment after digestion with the enzyme were the most porous and apparently had the largest surface area.) Qian et al (2010) pretreated starch with ultrasound before using an amylase to make porous starch. Z.…”
Section: Preparation Of Porous Starchmentioning
confidence: 99%
“…Porous starch can be obtained by physical, chemical, and biological methods. Ultrasonic and enzyme treatment has been mostly reported to produce porous starch [3,5]. It was reported that hollows or pores were formed on the surface and inside the granules, resulting in an increased surface area of the starch granules.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these shortcomings, various modified starch have been developed to obtain high surface areas and pore volumes. Porous starch is one such material which has received significant attention in recent years [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…And Qian, J., et al (2011) combined ultrasonic and enzymatic hydrolysis in an attempt to enlarge the pores. The problem on this treatment is on the determination of the optimum degree of enzymatic hydrolisis and also sometimes the adsorbent dissolves in the mixture creating an additional waste.…”
Section: Introductionmentioning
confidence: 99%